Food Security and Agricultural Sustainability - A Comparative Multi-Country Assessment of Critical Success Factors - Peter Nijkamp; Gabriella Vindigni (Tinbergen Institute, 2000)
This paper offers an overview of factors that are decisive forproductivity increase in the agricultural sector (bothfarming and agro-food). An attempt is made to explain differences intotal factor productivity in agriculture indifferent countries by means of meta-analysis, in particular, byusing rough set theory as a framework forcomparative study. The main aim is to derive the drivers of changesin agricultural food production with a view toconditional future predictions of an 'if...then' nature. The empiricalapplication to OECD countries is used toillustrate the potential of this new approach for identifyingcritical success factors in agriculture with a view tofuture food security objectives.
Keywords: 330; Ernährungssicherung; Landwirtschaft; Produktivität; Vergleich; OECD-Staaten